2D nanomaterials in biosensing: Synthesis, characterization, integration in biosensors and their applications - Desmond Lutomia; Renu Poria; Deepak Kala; Preeti Garg; Rupak Nagraik; Ankur Kaushal; Shagun Gupta; Deepak Kumar (Biosensors and Bioelectronics: X)
Recent advances in the synthesis of functional nanomaterials and precisely engineered nanostructures have opened up new avenues for the fabrication of viable biosensors for field analysis. Two-dimensional (2D) nanomaterials provide unique hierarchical structures, high surface area, and layered configurations with multiple length scales and porosity, and the possibility to create functionalities for targeted recognition at their surface. In addition to providing extra features like structural color, ordered morphological features, and the capacity to detect and react to external stimuli, such hierarchical structures provide opportunities to tune the characteristics of materials. Combining these distinctive qualities of the various nanostructure types and using them as a foundation for bimolecular assemblies can yield biosensing platforms with enhanced robustness, sensitivity, and selectivity for the detection of a wide range of analytes, as well as targeted recognition and transduction properties that can have a positive impact on numerous fields. This review describes the classification, synthesis and characterization of 2D nanomaterials and their functionalization. In addition, the merits of the 2D nanomaterials and their applications in health, environmental monitoring and food safety and control are covered. The final part anticipates the advancement of 2D nanomaterials in biosensors, challenges and future directions of 2D nanomaterials in biosensors.